1981
DOI: 10.1128/aac.20.4.547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenosine Monophosphate on the Reactivation of Latent Herpes Simplex Virus Type 1 Infections of Mice

Abstract: Adenosine monophosphate pretreatment of mice with latent herpes simplex virus type 1 infections significantly reduced the rate of reactivation of latent virus. Adenosine monophosphate pretreatment did not, however, eradicate latent virus.Recently,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The capacity of AMP to prevent both primary and recurrent herpes simplex virus type 1 (HSV- 1) infections resulting from inoculation of mouse ear pinnae has been previously reported (1). Here we report the results of therapeutic trials carried out in the same animal model system.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The capacity of AMP to prevent both primary and recurrent herpes simplex virus type 1 (HSV- 1) infections resulting from inoculation of mouse ear pinnae has been previously reported (1). Here we report the results of therapeutic trials carried out in the same animal model system.…”
mentioning
confidence: 65%
“…The mouse ear pinnae model of Hill et al (7,8) was utilized as described previously (1). For primary infection, the right ear pinnae of 4- A multiple-dose treatment regimen (four doses over a 24-h period) was used to determine the minimum dose required to completely inhibit the formation of primary lesions.…”
mentioning
confidence: 99%
“…Thus, we hypothesize that functional ADORA2A is required for the survival of SNU719 cells. A previous study reported that AMP could prevent the establishment of a latent infection and eradicate latent HSV-1 from the central nervous system [37]. This eradication of latent HSV-1 might be related to HSV-1 lytic reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Other observations suggest that cyclic nucleotides might also be involved in cellular control of the latent infection. 163 The existence of control mechanisms of cyclic nucleotides for selection of gene expression leading to induction of viral replication in somatic cell hybrids carrying but not expressing EBV genomes has been described. 164 Conversion of productive measles virus infection in neural cells to low or nonproductive infections may be achieved by treatment with drugs capable of modifying cyclic nucleotide metabolism.…”
Section: Influences Of the Cns And Neural Cells On Virus Infectionsmentioning
confidence: 99%